2009
DOI: 10.1142/s0218216509007154
|View full text |Cite
|
Sign up to set email alerts
|

Polyak–viro Formulas for Coefficients of the Conway Polynomial

Abstract: Abstract. We describe the Polyak-Viro arrow diagram formulas for the coefficients of the Conway polynomial. As a consequence, we obtain the Conway polynomial as a state sum over some subsets of the crossings of the knot diagram. It turns out to be a simplification of a special case of Jaeger's state model for the HOMFLY polynomial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…Let G be a Gauss diagram of a string link , see Figure 2(right) for an example. Kravchenko and Polyak [18], consider the following element of a quotient algebra Dias(n) [18, p. 306] of ZA j where the product is defined via tree grafting and relations 6 correspond to Loday's axioms of disassociative 5 We assume a slightly different convention than in [18], see Remark 4.1. 6 essentially encoding the Reidemeister moves algebras [22],…”
Section: Tree Invariantsmentioning
confidence: 99%
“…Let G be a Gauss diagram of a string link , see Figure 2(right) for an example. Kravchenko and Polyak [18], consider the following element of a quotient algebra Dias(n) [18, p. 306] of ZA j where the product is defined via tree grafting and relations 6 correspond to Loday's axioms of disassociative 5 We assume a slightly different convention than in [18], see Remark 4.1. 6 essentially encoding the Reidemeister moves algebras [22],…”
Section: Tree Invariantsmentioning
confidence: 99%
“…The three loop invariant is an invariant which is given by a Gauss diagram formula [27] with labeled pairs of regions (see below for definition). Much work has been done on finding Gauss diagram formulae for classical and virtual knot invariants [8,7,9,14,4,13]. The aim of this section is to define the three loop invariant, prove that it is an invariant of virtual knots, and provide some examples of its computation.…”
Section: The Three Loop Isotopy Invariantmentioning
confidence: 99%
“…There are many known extension of the Conway polynomial to virtual knots and virtual long knots. Some of them satisfy a straightforward generalization of the skein relation [4] while some do not [20]. Recently, Chmutov, Khoury, and Rossi showed that there exist two natural extensions of the Conway polynomial ∇ asc and ∇ desc to virtual long knots (see also, [5]) which satisfy a certain skein relation.…”
Section: Property 3: F M -Labelled Conway Polynomialmentioning
confidence: 99%
“…Related work for other knot polynomials has been done by Chmutov and Polyak [5] and Brandenbursky and Polyak [2]. The invariant ∇ asc may be defined as follows [4]. Let D be a Gauss diagram on R and x an arrow of D. We consider R to be identified with the x-axis in R 2 where it bounds the lower half-plane.…”
Section: Property 3: F M -Labelled Conway Polynomialmentioning
confidence: 99%